New climate leadership: "Yes, we can ... after all". The United States is caught between international ambitions and domestic challenges - Susanne Dröge; Sonja Thielges (Stiftung Wissenschaft und Politik (SWP), 2014)
In a push for climate protection in the US, the United States Environmental Protection Agency has proposed new CO2 emission limits for power plants. This is the next step in President Barack Obama's agenda on tackling climate change and the measures taken by the US administration are highly pertinent in the run-up to a new UN climate agreement in 2015. In June at the Bonn climate talks, the American push was welcomed. At the latest G7 summit a new climate deal was supported as well, and the US took the lead in bringing the issue forward. The EU has to balance its role as a key partner for developing countries under the UN framework with increasing its influence on key negotiators to promote climate protection as a global goal. (SWP Comments)
Keywords: 320